THE IMPACT OF CLIMATE CHANGE ON ECONOMIC GROWTH: A CASE OF TURKEY (Third Sector Social Economic Review, 2023)
Climate change is one of the most current issues discussed globally, with its causes and consequences. The relationship between carbon emission, which causes climate change, and economic growth makes climate change an economic problem. The relationship between economic growth and carbon emissions has been extensively discussed and empirically examined in national and international literature. However, when determining the relationship between economic growth and carbon emissions, many elements of macroeconomic performance should be evaluated together to consider the issue from a broad perspective and include its social nature. In this context, the research aims to investigate the economic impact of the carbon emission rate in Turkey by including unemployment and inflation, which are essential macroeconomic performance indicators. The data used were compiled from the World Bank database. The relationship between the variables was investigated with the Johansen Cointegration test. According to the findings, it was concluded that inflation and unemployment data have adverse effects on national income. It was determined that a unit shock in inflation and unemployment data decreased the national income by 0.225% and 0.425%, respectively. In addition, it was concluded that there is a positive relationship between carbon emissions and national income. For this reason, it is essential to encourage production techniques that reduce the carbon emission rate in the investments planned in the country.
Keywords: Climate Change; Economic Growth; Carbon Emission; Unemployment; Error Correction Model